Group Counseling Stress Inoculation Training Technique To Increase Academic Distress Tolerance Through Hardiness in Students (Jurnal Bimbingan Konseling, 2019)
The purpose of this study was to examine the effectiveness of group counseling with stress inoculation training techniques to increase academic distress tolerance through hardiness. This study used a pre-test – post-test control group design involving 14 people who were selected purposively from 70 students. The data analysis technique used is bootstraping. The results showed that group counseling with stress inoculation training techniques proved effective in increasing tolerance of academic distress through hardiness. This finding proves that group counseling stress inoculation training techniques are effective for increasing tolerance of distress through hardiness in students.